THE IMPLEMENTATION OF E-GOVERNMENT THROUGH THE VILLAGE INFORMATION SYSTEM (SID) IN KUREKSARI VILLAGE, WARU DISTRICT, SIDOARJO REGENCY - Purnomo, Fellita Intan Putri; Mursyidah, Lailul (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the implementation of the Village Information System (SID) in Kureksari Village in accordance with Sidoarjo Regent Regulation Number 98 of 2022, focusing on the factors that support and hinder the provision of transparent information services for the community. Method: A qualitative descriptive case study approach was employed, with data collected through observation, interviews, and documentation, and analyzed using Indrajit’s (2005) balanced e-government scorecard framework, which includes the dimensions of benefits, efficiency, participation, transparency, and change management. Results: The findings reveal that supporting factors include adequate budget allocation for facilities, infrastructure, and SID procurement, as well as strong participation from community organizations and NGOs that actively contribute to system utilization. However, inhibiting factors persist, including ineffective website implementation, limited technological skills among village staff due to insufficient training, and frequent system errors caused by overlapping electronic service platforms. Novelty: This research contributes by applying the balanced e-government scorecard to evaluate SID at the village level, offering new insights into how financial resources and community participation can strengthen implementation, while highlighting the urgent need for capacity building and system integration to ensure more effective and transparent village governance.